Studies on the translocation of potato viruses X and Y in potatoes - and B.B. NAGAICH, R.B.S. SAGAR, HARI OM AGRAWAL (Indian Phytopathology, 2002)
Translocation of Potato Virus X (PVX) and Potato Virus Y (PVY) in potato varieties Kufri Chandramukhi, Kufri Jyoti and Kufri Sindhuri was studied. PVX and PVY took 4, 6, 8 and 4, 4, 6 days in Kufri Chandramukhi, Kufri Sindhuri and Kufri Jyou, respectively to move from inoculated leaflet into stem. The viruses reached the tubers after 6, 8, la and 6, 6, 8 days, respectively. Uninfected pieces of stem occurred between infected pieces in all three potato varieties infected with each of the two viruses. Variety Kufri Chandramukhi proved best followed by Kufri Sindhuri and Kufri Jyoti for translocation of both viruses. PVY was slightly faster in translocation and gave larger number of tuber infection when compared to PVX.